PESAN MORAL DALAM SUREK UGI MEONGPALO KARELLAE (Moral Message in Sureq Ugi Meongpalo Karellae) - Jemmain Jemmain (SAWERIGADING, 2009)
Surek Ugi Meongpalo Karellae is a culture product in the literature. Form thatdescribes human and humanity problem it contains lefe problems it is explored by the character Meongpalo Karellae who always protects and guards Datunna Sangiangseri (King of rice plant). This literary work also implies any knowledge relating to universal, moral messages, philosophy, bekef, hirtory, and ather elements that conveys unvaluable message.